Minmax robustness for multi-objective optimization problems - Ehrgott, Matthias; Ide, Jonas; Schöbel, Anita (European journal of operational research, 2014)
•Minmax robustness is extended to multi-objective optimization.•The concept of minmax robust efficiency is introduced.•Weighted sum scalarization and epsilon-constraints are adjusted to the new concept.•Problems with objective-wise uncertainty are investigated more closely.•The concepts are illustrated with a few LP-examples. In real-world applications of optimization, optimal solutions are often of limited value, because disturbances of or changes to input data may diminish the quality of an optimal solution or even render it infeasible. One way to deal with uncertain input data is robust optimization, the aim of which is to find solutions which remain feasible and of good quality for all possible scenarios, i.e., realizations of the uncertain data. For single objective optimization, several definitions of robustness have been thoroughly analyzed and robust optimization methods have been developed. In this paper, we extend the concept of minmax robustness (Ben-Tal, Ghaoui, & Nemirovski, 2009) to multi-objective optimization and call this extension robust efficiency for uncertain multi-objective optimization problems. We use ingredients from robust (single objective) and (deterministic) multi-objective optimization to gain insight into the new area of robust multi-objective optimization. We analyze the new concept and discuss how robust solutions of multi-objective optimization problems may be computed. To this end, we use techniques from both robust (single objective) and (deterministic) multi-objective optimization. The new concepts are illustrated with some linear and quadratic programming instances.